Effect of different feeding levels of turmeric and amla on performance of broilers - A.V. RATHOD; S.K. PANDEY, GYAN CHANDRA S.H. MANE, S.A. DHAGE (Indian Journal of Animal Production and Management, 2020)
An experiment was conducted with two types of herbal products (amla and turmeric) either alone or in combination in seven dietary treatments to study the growth performance in broilers. The treatment groups consisted of control (T0), 0.25% turmeric (T1), 0.5% turmeric (T2), 0.25% amla (T3), 0.5% turmeric (T4), 0.25% turmeric+amla (T5) and 0.5% turmeric+amla (T6) were included in broiler diet. The different types of herbals feed supplement either alone or in combination at 0.25% and 0.5% levels in broiler diet give better growth performance of body weight gain or feed conversion ratio. The feed conversion ratio increased which were significant in broilers fed with different herbals either alone or in combination compared to control. The results suggested that herbals like amla and turmeric can be supplemented in broiler feeds as they have direct effect on improving body weight gain, feed conversion ratio and better economic return.